Communicative approach based on gender towards the sexual orientation in educational sports centers of Santiago de Cuba - Alina Bestard Revilla (Podium, 2020)
Human beings have learned to live with, understand and even act upon the diversity that exists in the world. However, it is still a little difficult to reason about those differences that have to do with people. The objective of this study is to design communicational educational actions to provide treatment and pedagogical orientation to individual differences and sexual diversity in women's softball athletes at the "Orestes Acosta" Initiation Sport School (EIDE in Spanish) in Santiago de Cuba. From the diagnosis applied to a sample of 27 athletes from the women's softball team of the mentioned institution and scientific observation, it was possible to learn about difficulties with the acceptance of sexual diversity in training, competitions, and other related sports activities. To carry out this study, methods, techniques, and instruments were applied for the diagnosis of the approach to sexual diversity such as the survey, interview, and group assessment test (desired interrelationships). As a result, a didactic proposal is offered that contemplates some educational aspects to be taken into account in the treatment of athletes with sexual diversity, such as: personality traits of the athletes, levels of sexual information established according to the age of the athlete, respect for their sexual orientation, depth in the analysis of the situation of their sexual diversity, response of the athlete to the treatment offered, linkage of the school, family and community, need for interdisciplinary work of the teaching staff for the adequate sexual orientation of the athletes.